(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the pivotal role and profound importance of human feelings in various activities, highlighting how emotions influence decision-making, motivation, and overall performance. It delves into the psychological and physiological mechanisms through which feelings impact our actions, as well as the ways in which understanding and managing emotions can enhance productivity and personal well-being. Through a comprehensive review of existing literature and empirical studies, the article examines the interplay between emotional intelligence and effective functioning in both personal and professional contexts. The findings underscore the necessity of fostering emotional awareness and regulation skills to optimize human potential and activity outcomes.